Landscape Photography, National Parks, and Settler Colonial Nationalism - Devadoss, Christabel (GeoHumanities, 2025)
Research has been critical of photography as a patriarchal and colonial tool while also focusing on representation of outdoor spaces as white. While research has examined patriarchy and colonialism in visual historical practice, it has not explicitly addressed the connections between US landscape photography and the foundations of national parks and public lands. This paper discusses how photography, not just as art but as a representational practice, intersects with nationalism in settler colonial spaces and subsequently impacts public imagination and participation in such places. Framing of national lands concurrently impacts the field of landscape photography and shapes societal expectations of visual ownership in the US. Drawing from public sources like the National Park Service (NPS) signage and websites, historical representation, and visual public media on the US National Parks (like PBS), I demonstrate how national park visual discourses, past and present, intricately intertwine with (white) nationalist imaginings that intersect with settler colonial ideologies, impacting the historical and current practice of US landscape photography.